2008
DOI: 10.1007/s12010-008-8359-0
|View full text |Cite
|
Sign up to set email alerts
|

Yarrowia lipolytica Growth Under Increased Air Pressure: Influence on Enzyme Production

Abstract: Improvement of microbial cell cultures oxygenation can be achieved by the increase of total air pressure, which increases oxygen solubility in the medium. In this work, a pressurized bioreactor was used for Yarrowia lipolytica batch cultivation under increased air pressure from 1 to 6 bar. Cell growth was strongly enhanced by the pressure rise. Fivefold and 3.4-fold increases in the biomass production and in specific growth rate, respectively, were observed under 6 bar. The increase of oxygen availability caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…On the other hand, a good agitation favors turbulence which leads to a decrease of the thickness of the liquid layer on the gas/liquid interface, reducing the resistance to oxygen mass transfer. This statement is in accordance with the conclusions reported by Lopes et al [9], who recorded an increase of 96 % in lipase activity values when using 5 bar air pressure instead of 1 bar pressure during the culture of Yarrowia lipolytica. In the same way, Deive et al [41] observed higher lipolytic enzyme levels in a stirred-tank bioreactor compared to an air-lift one.…”
Section: Bioreactor Culturesupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, a good agitation favors turbulence which leads to a decrease of the thickness of the liquid layer on the gas/liquid interface, reducing the resistance to oxygen mass transfer. This statement is in accordance with the conclusions reported by Lopes et al [9], who recorded an increase of 96 % in lipase activity values when using 5 bar air pressure instead of 1 bar pressure during the culture of Yarrowia lipolytica. In the same way, Deive et al [41] observed higher lipolytic enzyme levels in a stirred-tank bioreactor compared to an air-lift one.…”
Section: Bioreactor Culturesupporting
confidence: 93%
“…However, a considerable amount of the research carried out to date has focused on small-scale procedures, while less information is available on the particular characteristics of lipolytic enzyme biosynthesis in bioreactors and the feasibility of diverse culture modes, such as batch, fed-batch, or continuous systems [6][7][8]. Over the last few months, research concerning lipase production by yeasts and fungi in bioreactors has been employed to obtain high levels of lipase production, thus demonstrating the interest that the scale-up of this kind of biological process is triggering nowadays and then encouraging further research in this field [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the microbial sources were chosen which could be feasible for induction of SOD subjected to ROS stress and the large scale production of SOD. The proliferation of SOD was induced by increase in the air pressure from 1 to 6 bar in a batch cultivation of Yarrowia lipolytica [13].…”
Section: Industrial Applications Of Sodmentioning
confidence: 99%
“…It is known that lipolytic activity of Y. lipolytica is influenced by many factors, including: the type and concentration of the carbon source in the medium, the pH value of the culture, the oxygen partial pressure, the temperature of the culture and the amount of inoculum 24,25 . Furthermore, cell activity is closely associated with the growth phase of microorganism.…”
Section: Lipolytic Activity Of Yeast Cells and Supernatant During Batmentioning
confidence: 99%